“To Get Those Plants ... Likely to Prove Interesting at Edinburgh": Robert Brown of Perth and James McNab’s North American Tour of 1834 - Hardy, Graham (Sibbaldia: the International Journal of Botanic Garden Horticulture, 2011)
Robert Brown and James McNab are introduced and the purposes of their journey in 1834 are explained. Extracts from the diaries written by McNab which might be of particular interest to horticulturists are reproduced. The details of the itinerary and a seed list of species collected are also included as appendices.